Pengendalian Intern Terhadap Sistem Pemungutan Pajak Reklame Pada Badan Pendapatan Pengelolaan Keuangan Dan Aset Daerah (Bppkad) Kabupaten Temanggung - Arin Nuraeni; Siti Mutmainah (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2018)
Good internal control is very important to achieve the main goals of a company, therefore the purpose of this Final Project is to know the application of internal control structure of advertisement tax collection system at Badan Pendapatan Pengelolaan Keuangan dan Aset Daerah (BPPKAD) Kabupaten Temanggung and to identify the conformity with the components control according to PP Nomor 60 Tahun 2008 about The Government Internal Control System. The data used are qualitative data, primary data, and secondary data. Data collection using questionnaire method, interview, observation, and literature study. The writing methods of this final project are description and exposition. The result of this Final Project shows that the application of internal control of advertisement tax collection system at BPPKAD Temanggung Regency has been run effectively and has been run in accordance with the design of components of Government Internal Control System (SPIP). In the component of control activities that is the separation of duties, there are still dual positions. To reduce the misuse of authority, BPPKAD Kabupaten Temanggung should add additional employees.